Pengembangan Kompetensi Dosen di Sekolah Tinggi Agama Islam Riyadhul Jannah Jalancagak Subang Jawa Barat - Hisny Fajrussalam; Fitria Zulfa; Indra Saeful Hidayat; Ajat Saputra (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2020)
The research aims to describe the competence development of lecturers at the Riyadhul Jannah Islamic College, Jalancagak Subang West Java. The study was conducted with a qualitative approach. Data obtained by observation, interview, and documentation techniques. The results obtained were the competence development of lecturers carried out by the Riyadhul Jannah Islamic Islamic College consisting of four variables, namely 1) communication and motivation; 2) lecturer professionalism; and 3) conflict management. Reformulation is needed in the lecturer development conducted by the Riyadhul Jannah Islamic College in order to improve the quality of higher education. Some homework also needs to be carried out to better support the process of lecturer development competence so that quality learning processes are achieved, namely re-selection of lecturers who are not linear and lecturer honorarium enhancement. Penelitian ini bertujuan untuk mendeskripsikan pengembangan kompetensi dosen di Sekolah Tinggi Agama Islam Riyadhul Jannah Jalancagak Subang Jawa Barat. Penelitian dilakukan dengan pendekatan kualitatif. Data diperoleh dengan teknik observasi, wawancara, dan dokumentasi. Hasil yang diperoleh adalah pengembangan kompetensi dosen yang dilakukan oleh Sekolah Tinggi Agama Islam Riyadhul Jannah yang terdiri dari empat variabel, yaitu 1) komunikasi dan motivasi; 2) profesionalisme dosen; dan 3) manajemen konflik. Diperlukan reformulasi dalam pengembangan kompetensi dosen yang dilakukan oleh Sekolah Tinggi Agama Islam Riyadhul Jannah dalam rangka meningkatkan kualitas pendidikan tinggi. Beberapa pekerjaan rumah juga perlu dilakukan untuk lebih mendukung proses pengembangan kompetensi dosen sehingga proses pembelajaran yang berkualitas tercapai, yaitu pemilihan ulang dosen yang tidak linier dan peningkatan honorarium dosen. Kata Kunci, pengembangan komepetensi dosen, perguruan tinggi Islam